2016
DOI: 10.1001/jamaneurol.2015.4388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Functional Motor Outcomes of Enterovirus 71 Neurological Disease in Children

Abstract: IMPORTANCE Enterovirus 71 (EV71) causes a spectrum of neurological complications with significant morbidity and mortality. Further understanding of the characteristics of EV71-related neurological disease, factors related to outcome, and potential responsiveness to treatments is important in developing therapeutic guidelines. OBJECTIVE To further characterize EV71-related neurological disease and neurological outcome in children. DESIGN, SETTING, AND PARTICIPANTS Prospective 2-hospital (The Sydney Children's H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 39 publications
12
84
3
1
Order By: Relevance
“…As the major causative agent among the spectrum of HFMD-causing pathogens in different areas of mainland of China, EV-A71 was believed to be the pathogen associated with most of the severe cases and almost all of the fatal cases, while CV-A16 was thought to be responsible for a sizeable proportion of the mild HFMD cases[4749]. Similarly, in this study, EV-A71 and CV-A16 were the two most dominant pathogens in the Shijiazhuang City, while CV-A10 was the third most frequent pathogen, accounting for 4.7% of the laboratory-confirmed cases.…”
Section: Discussionmentioning
confidence: 99%
“…As the major causative agent among the spectrum of HFMD-causing pathogens in different areas of mainland of China, EV-A71 was believed to be the pathogen associated with most of the severe cases and almost all of the fatal cases, while CV-A16 was thought to be responsible for a sizeable proportion of the mild HFMD cases[4749]. Similarly, in this study, EV-A71 and CV-A16 were the two most dominant pathogens in the Shijiazhuang City, while CV-A10 was the third most frequent pathogen, accounting for 4.7% of the laboratory-confirmed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EV71 infection induced an inflammatory response and even a systemic dysregulation of the immune system in humans [41–42]. Recent studies show that Th22 cells, identified as a distinct subset of the Th cell family by specific production of IL-22, play crucial roles in regulating immune responses and are closely associated with multiple diseases, such as skin inflammation, infections, autoimmune diseases, and tumors [2125].…”
Section: Discussionmentioning
confidence: 99%
“…The outbreak in Catalonia originated from EV-A71 (from species A) or EV71 (from the classic classification); in many current publications, the virus is named using the latter taxonomy. 6 EV-A71 is divided into 6 genotypes (genogroups), A to F, but only B and C have been associated with outbreaks. Among the sub-genotypes, B4, B5 and C4 circulate mainly in Asia, while C1 and C2 are found primarily in Europe.…”
Section: Enterovirusmentioning
confidence: 99%
“…14,15 (2) Serious manifestations: neonatal sepsis-like illness; neurological syndromes such as septic meningitis, meningoencephalitis, cerebellitis and encephalitis (particularly in the form of rhombencephalitis), myelitis, acute flaccid paralyses, acute neurogenic pulmonary oedema and cardiac manifestations, such as myocarditis and pericarditis. 4,6,8,[16][17][18] …”
Section: Clinical Forms Of Enteroviruses: From Mild To Severementioning
confidence: 99%